2016
DOI: 10.21511/ppm.14(3-1).2016.08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of integrated reporting ratings, CEO age, and years of experience on the share price of top 106 JSE listed companies

Abstract: AUTHORSPatient Rambe Tonderayi B. Mangara ARTICLE INFOPatient Rambe and Tonderayi B. Mangara (2016). Influence of integrated reporting ratings, CEO age, and years of experience on the share price of top 106 JSE listed companies.Influence of integrated reporting ratings, CEO age, and years of experience on the share price of top 106 JSE listed companies Abstract Integrated corporate reporting (ICR), which entails the process of compiling, documenting and reporting on company's resources, its ongoing relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…Os resultados dessas pesquisas são inconclusivos, porém existem achados que mostram que a qualidade do RI está associada de forma positiva à avaliação das empresas (Q de Tobin) (Barth et al, 2017;Lee & Yeo, 2016), correspondendo a um aumento no preço de mercado das ações (Rambe & Mangara, 2016), na melhora da liquidez, na precisão de previsão dos analistas e na redução do custo de capital (Barth et al, 2017;Zhou et al, 2017).…”
Section: Estudos Anterioresunclassified
See 1 more Smart Citation
“…Os resultados dessas pesquisas são inconclusivos, porém existem achados que mostram que a qualidade do RI está associada de forma positiva à avaliação das empresas (Q de Tobin) (Barth et al, 2017;Lee & Yeo, 2016), correspondendo a um aumento no preço de mercado das ações (Rambe & Mangara, 2016), na melhora da liquidez, na precisão de previsão dos analistas e na redução do custo de capital (Barth et al, 2017;Zhou et al, 2017).…”
Section: Estudos Anterioresunclassified
“…Pesquisas anteriores investigaram a relação entre o nível de qualidade do Relato Integrado e o valor de mercado das empresas, o desempenho econômico e financeiro e a precisão de previsão dos analistas, no contexto sul africano (Rambe & Mangara, 2016;Barth, Cahan, Chen & Venter, 2017;Matemane & Wentzel, 2019). Já outros estudos, considerando uma amostra internacional mais ampla, investigaram o impacto da qualidade da divulgação do Relato Integrado no desempenho da empresa, em seu valor de mercado e em seu custo de capital (Pavlopoulos;Magnis & Iatridis, 2019;Vitolla;Salvi;Raimo;Petruzzella & Rubino, 2020).…”
Section: Introductionunclassified
“…Similarly, in their research on the influence of individual executives on corporate financial reporting, Plöckinger, Aschauer, Hiebl, and Rohatschek (2016) noted that older CEOs are less often involved in fraudulent actions. Connecting age and experience with firm performance, Rambe and Mangara (2016) analyzed the impact of integrated reporting ratings (IRR), the CEO's age, and the individual's tenure as CEO on the company's share price. Their findings showed that share price of a company tends to increase with an increase in IRR, CEO age, and CEO years of experience (Rambe & Mangara, 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Connecting age and experience with firm performance, Rambe and Mangara (2016) analyzed the impact of integrated reporting ratings (IRR), the CEO's age, and the individual's tenure as CEO on the company's share price. Their findings showed that share price of a company tends to increase with an increase in IRR, CEO age, and CEO years of experience (Rambe & Mangara, 2016). This leads to the argument that an older CFO will have more experience to manage the financial operations of a firm.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Existem diversas pesquisas que comprovam alguns benefícios elencados na literatura para adoção do RI, como redução no custo do capital (García-Sánchez & Nogueira-Gómez, 2017;Zhou et al, 2017), melhoria no preço da ação (Rambe & Mangara, 2016;Giorgino et al, 2017), aumento do lucro e do valor contábil (Baboukardos & Rimmel, 2016), ou ainda, na divulgação de RI com quali-dade, como melhoria na avalição da empresa e no processamento de informações (Lee & Yeo, 2016) e no valor da empresa, na liquidez, no fluxo de caixa futuro esperado e na eficiência dos investimentos (Barth et al, 2017).…”
Section: Fundamentação Teóricaunclassified